Students Satisfaction with Inasis Telekom Malaysia (TM) Facilities in Universiti Utara Malaysia (UUM) - Abu Bakar, Mohamad Firdaus; Othman, Zainudin (Universiti Utara Malaysia, 2019)
This paper aims to investigate student’s satisfaction with the facilities provided by the Inasis Telekom Malaysia (TM) in Universiti Utara Malaysia (UUM). A total of 100 questionnaires were distributed to students staying at Inasis Telekom Malaysia (TM). The data were analyzed using the descriptive statistics. This study will be provided a new knowledge pertaining to the service provided by Inasis Telekom Malaysia (TM) UUM for their students in the Inasis itself. The results did support the framework of the study. Based on the results, it shows that overall students perceive service provides at Inasis to be good. The analysis also indicate the hostel management, must accept the importance of service quality in student housing facilities as an effective medium to attract students to enroll in UUM. If not, a slightly decreased in the overall perception level of students toward the service facilities may lead to the negative perception toward the university.